Investigation of air pollution and noise on progression of thoracic aortic calcification: results of the Heinz Nixdorf Recall Study. (29th August 2020) - Hennig, Frauke; Moebus, Susanne; Reinsch, Nico; Budde, Thomas; Erbel, Raimund; Jöckel, Karl-Heinz; Lehmann, Nils; Hoffmann, Barbara; Kälsch, Hagen; ,
Abstract: Aims: Air pollution and noise are potential risk factors for subclinical atherosclerosis. Longitudinal analyses, especially on the interplay of these environmental factors, are scarce and inconsistent. Hence we investigated long-term traffic-related exposure to air pollution and noise with the development and progression of thoracic aortic calcification, a marker of subclinical atherosclerosis. Methods: We used baseline (2000–2003) and follow-up (2006–2008) data from the German Heinz Nixdorf Recall cohort study, including 4814 middle-aged adults. Residence-based air pollution (PM2.5 (aerodynamic diameter ≤ 2.5 µm), PM10, nitrogen dioxide and particle number), and noise was assessed with dispersion models. Thoracic aortic calcification was quantified from non-contrast enhanced electron beam computed tomography. The presence and extent of thoracic aortic calcification progression were analysed with multiple logistic and linear regression models, respectively, adjusting for age, sex, lifestyle variables, socioeconomic status and respective co-exposure. Results: We observed no association in the full study sample ( n = 3155, mean age 59.1 (±7.6) years, 52.8% women). While an interquartile range in particle number and night-time noise yielded odds ratios of 1.20 (1.03, 1.40) and 1.21 (1.00, 1.46) for binary thoracic aortic calcification progression, and 0.02 (–0.01, 0.05) and 0.04 (0.00, 0.07) higher growth rates of thoracic aortic calcification in participants with baseline thoracic aortic calcification less than 10, negative findings were observed in those with baseline thoracic aortic calcification of 10 or greater. Results were similar for other pollutants and daytime noise. Conclusion: Our study shows no overall associations. Subgroup analyses suggest independent associations of traffic-related air pollution and noise with the development and progression of subclinical atherosclerosis in participants with no or minor thoracic aortic calcification at baseline, in contrast to negative findings in those with advanced calcification.